THE ROLE OF AGRICULTURE IN THE DEVELOPMENT OF THE EXPORT POTENTIAL OF THE REPUBLIC OF UZBEKISTAN (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
Agriculture plays a pivotal role in the economic landscape of the Republic of Uzbekistan, significantly contributing to its export potential. As one of the key sectors in the country, agriculture not only provides employment for a substantial portion of the population but also serves as a cornerstone for economic growth and development.This research explores how agricultural practices, crop diversification, and modernization efforts can enhance Uzbekistan’s position in global markets.